Discovery of Quercetin and Its Analogs as Potent OXA-48 Beta-Lactamase Inhibitors - Zhang, Yuejuan; Chen, Cheng; Cheng, Bin; Gao, Lei; Qin, Chuan; Zhang, Lixia; Zhang, Xu; Wang, Jun; Wan, Yi (Frontiers in Pharmacology, 2022)
Carbapenem resistance in Enterobacteriaceae caused by OXA-48 β-lactamase is a growing global health threat and has rapidly spread in many regions of the world. Developing inhibitors is a promising way to overcome antibiotic resistance. However, there are few options for problematic OXA-48. Here we identified quercetin, fisetin, luteolin, 3’,4’,7-trihydroxyflavone, apigenin, kaempferol and taxifolin as potent inhibitors of OXA-48 with IC50 values ranging from 0.47 to 4.54 μM. Notably, structure-activity relationship revealed that the substitute hydroxyl groups in the A and B rings of quercetin and its structural analogs improved inhibitory effect against OXA-48. Mechanism studies including enzymatic kinetic assay, isothermal titration calorimetry (ITC) and surface plasmon resonance (SPR) analysis demonstrated that quercetin reversibly inhibited OXA-48 through a noncompetitive mode. Molecular docking suggested that hydroxyl groups at the 3’, 4’ and 7 positions in flavonoids formed hydrogen-bonding interactions with the side chains of Thr209, Ala194, and Gln193 in OXA-48. Quercetin, fisetin, luteolin, and 3’,4’,7-trihydroxyflavone effectively restored the antibacterial efficacy of piperacillin or imipenem against E. coli producing OXA-48, resulting in 2- to 8-fold reduction in MIC. Moreover, quercetin combined with piperacillin showed antimicrobial efficacy in mice infection model. These studies provide potential lead compounds for the development of β-lactamase inhibitors and in combination with β-lactams to combat OXA-48 producing pathogen.